Eucalyptus urograndis stem proteome is responsive to short-term cold stress - Leonardi, Gabriela de Almeida [UNESP]; Carlos, Natália Aparecida [UNESP]; Mazzafera, Paulo; Balbuena, Tiago Santana [UNESP] (Soc Brasil Genetica, 2015)
Eucalyptus urograndis is a hybrid eucalyptus of major economic importance to the Brazilian pulp and paper industry. Although widely used in forest nurseries around the country, little is known about the biochemical changes imposed by environmental stress in this species. In this study, we evaluated the changes in the stem proteome after short-term stimulation by exposure to low temperature. Using two-dimensional gel electrophoresis coupled to high-resolution mass spectrometry-based protein identification, 12 proteins were found to be differentially regulated and successfully identified after stringent database searches against a protein database from a closely related species (Eucalyptus grandis). The identification of these proteins indicated that the E. urograndis stem proteome responded quickly to low temperature, mostly by down-regulating specific proteins involved in energy metabolism, protein synthesis and signaling. The results of this study represent the first step in understanding the molecular and biochemical responses of E. urograndis to thermal stress.
Keywords: Abiotic stress; Mass spectrometry; Omics; Proteomics